On some Bees of the Genus Andrena from the Islands Crete and Cyprus (Hymenoptera: Apoidea). - Mavromoustakis, George A. (Contributions to Entomology = Beiträge zur Entomologie, 1956)
Nomenclatural Acts neocypriaca Mavromoustakis, 1956 (Andrena), spec. n. polemediana Mavromoustakis, 1956 (Andrena), spec. n.